Application of a new integrated low-profile anterior plate and cage system in single-level cervical spondylosis: a preliminary retrospective study - Leixin Wei; Chen Xu; Minjie Dong; Yibo Dou; Ye Tian; Huiqiao Wu; Xiaodong Wu; Xinwei Wang; Huajiang Chen; Xiaolong Shen; Peng Cao; Wen Yuan (Journal of Orthopaedic Surgery and Research, 2022)
Abstract Background Although ACDF has been widely used in treating cervical spondylosis and related diseases, the complications along with this anterior surgical technique have hindered its application and affected the postoperative outcome of the patients. Here, we investigated the clinical and radiological outcomes of a new integrated low-profile anterior plate and cage system for anterior cervical discectomy and fusion (ACDF) in treating cervical spondylosis. Methods A total of 96 cervical spondylosis patients who underwent single-level ACDF between 2018 to 2020 in our institute were enrolled. There were 28 patients using the new implants and 68 patients using the zero-profile (Zero-P) implants. The Japanese Orthopedic Association (JOA) score and the visual analog scale (VAS) were used to evaluate the clinical outcomes. The cervical and segmental Cobb angle and range of motion (ROM) were used to assessed the radiological outcomes. Incidence of complications were also recorded. All data were recorded at pre-operation, 6-month and 12-month post-operation. Results All patients were followed-up for at least 1-year, the mean follow-up time was over one year. The fusion rate was similar in the two groups. There was no significant difference in the postoperative JOA score recovery rate, postoperative VAS score of neck and arm pain, postoperative ROM, and incidence of complications between two groups (P > 0.05). However, postoperative cervical and segmental Cobb angle were better maintained in the new low-profile implant group compared to Zero-P group. Conclusions The clinical outcomes of the new low-profile implant were satisfactory and comparable to that of zero-profile system. It may have advantages in improving and maintaining the cervical lordosis, and can be an alternative device for single-level cervical spondylosis treated with ACDF.